2020
DOI: 10.1093/mnras/staa3885
|View full text |Cite
|
Sign up to set email alerts
|

A physico-chemical model to study the ion density distribution in the inner coma of comet C/2016 R2 (Pan-STARRS)

Abstract: The recent observations show that comet C/2016 R2 (Pan-Starrs) has a unique and peculiar composition when compared with several other comets observed at 2.8 au heliocentric distance. Assuming solar resonance fluorescence is the only excitation source, the observed ionic emission intensity ratios are used to constrain the corresponding neutral abundances in this comet. We developed a physico-chemical model to study the ion density distribution in the inner coma of this comet by accounting for photon and electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 102 publications
1
7
0
Order By: Relevance
“…The revised values for the fluorescence efficiencies computed in this work imply some revisions for the relative abundances of N + 2 compared to CO + , for which they have been published and based on the calculations of Lutz et al (1993). 2019) reported a N + 2 /CO + ratio of 0.06 ± 0.01, which agrees well with Cochran & McKay (2018b,a) and Raghuram et al (2021). Because this ratio is proportional to the ratio of the CO + fluorescence efficiency to the efficiency of N + 2 , the final N + 2 /CO + ratio is expected to change from 6% to 8.8% if g N + 2 changes from 7 × 10 −2 to 4.77 × 10 −2 photon s −1 ion −1 (i.e., the value computed for the time of observation scaled to 1 au).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The revised values for the fluorescence efficiencies computed in this work imply some revisions for the relative abundances of N + 2 compared to CO + , for which they have been published and based on the calculations of Lutz et al (1993). 2019) reported a N + 2 /CO + ratio of 0.06 ± 0.01, which agrees well with Cochran & McKay (2018b,a) and Raghuram et al (2021). Because this ratio is proportional to the ratio of the CO + fluorescence efficiency to the efficiency of N + 2 , the final N + 2 /CO + ratio is expected to change from 6% to 8.8% if g N + 2 changes from 7 × 10 −2 to 4.77 × 10 −2 photon s −1 ion −1 (i.e., the value computed for the time of observation scaled to 1 au).…”
Section: Discussionsupporting
confidence: 85%
“…The N + 2 ions located along the line of sight correspond to different elapsed times since their creation, mainly by photoionization (see Raghuram et al 2021 for more details about an estimate of the different processes leading to the formation of N + 2 ions in the inner coma of comet C/2016 R2). Modeling the resulting spectrum that is created by ions with different emission spectra is therefore difficult.…”
Section: Discussionmentioning
confidence: 99%
“…For the CO2 + A2Π −X2Π (0,0) band near 3500 Å we assumed a simple Haser profile with one component, CO2 being the parent. The time scale and fluorescence efficiency are taken from 38,39 . The profile distribution was integrated over the area of the slit of the spectrograph and compared to the observed flux of the bands to yield the production rate.…”
mentioning
confidence: 99%
“…Whether the ions can be used to derive the abundance of neutral species also depends on if the ions are mainly produced through photoionization of the corresponding neutrals or if they are produced through other processes like ion-neutral chemistry. For example, for comet C/2016 R2 (PANSTARRS), it has be shown that the CO + 2 was also produced through charge exchange between CO + and CO 2 , indicating that for comets with very high CO abundances, CO + 2 might not be a reliable indicator of the CO 2 abundance [37]. Nevertheless, in spite of these caveats, ions emission bands observed at optical wavelengths have proven very useful in the past to estimate the relative abundance of difficult to observe neutrals in the coma of comets, and in particular the N 2 /CO ratio [31,32,33].…”
Section: Measuring the N 2 /Co Ratio In Cometsmentioning
confidence: 99%

Cometary science with CUBES

Opitom,
Snodgrass,
La Forgia
et al. 2022
Preprint
Self Cite